2005
DOI: 10.1097/01.mpg.0000155565.64279.05
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dexamethasone on Antral Mucosal Protein and Gastric Development in Postnatal Rats

Abstract: Increases in AMP-18, pepsin and glandular stomach mass during normal postnatal development suggest that AMP-18 might be involved in gastric maturation, at least in the glandular portion. Dexamethasone induction of pepsin and AMP-18 and the subsequent increase in glandular stomach mass also suggest a possible role for AMP-18 in glandular stomach maturation. Dexamethasone apparently acts through the type II corticosteroid receptor to induce AMP-18.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
3
0
2
Order By: Relevance
“…These physiological functions and expression location of GKN1 are similar to trefoil factor 1, which plays an important cytoprotective role in the gastric mucosa (23,24). In addition, GKN1 is involved in gastric maturation in postnatal rats and protection of colonic epithelial cells (25,26). It is noted that another member of the gastrokine family, GKN2, has been viewed as a protective factor in gastric mucosa (27,28).…”
Section: Discussionmentioning
confidence: 93%
“…These physiological functions and expression location of GKN1 are similar to trefoil factor 1, which plays an important cytoprotective role in the gastric mucosa (23,24). In addition, GKN1 is involved in gastric maturation in postnatal rats and protection of colonic epithelial cells (25,26). It is noted that another member of the gastrokine family, GKN2, has been viewed as a protective factor in gastric mucosa (27,28).…”
Section: Discussionmentioning
confidence: 93%
“…27,28 A role in defending the mucosa has been reported by Toback et al who showed that GKN1 promoted epithelial restoration in gastric cell culture. 13 In addition, it was reported that GKN1 might be involved in maturation, at least in the glandular portion of the gastric mucosa 29 playing a pivotal role in cell differentiation. [30][31][32] Thus, it is reasonable to hypothesize that in the presence of gastric offending agents, not necessarily implicated in the carcinogenesis process, the resident injured epithelial cells lose the ability to express GKN1.…”
Section: Discussionmentioning
confidence: 99%
“…11 However, these observations have been based on data obtained primarily from biochemical or electrophysiological studies of stripped mucosa from experimental animals and supported by reports showing the presence of GR RNA, protein or ligandbinding in these tissue samples in toto. 6,9,12 Convincing in situ studies of the expression patterns of GR in the heterogeneous cell components of the human digestive system, critical to understanding and validating its roles in these organs, are lacking. 11 GR has been shown to be frequently present in cell lines derived from digestive tract carcinomas [13][14][15][16][17][18][19] and in a high percentage of primary tissues of several types of digestive system tumours.…”
Section: Introductionmentioning
confidence: 99%